Pendampingan Literasi Media untuk Edukasi Anak-Anak - Rachman, Rio Febriannur; Ishari, Nurhafid; Nuha, Ahmad Arif Ulin; Fahma, Alhimni (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The development of digital technology has influenced children’s learning patterns and information consumption, including within non-formal religious education settings such as Taman Pendidikan Al-Qur’an (TPQ). Although digital media have the potential to serve as educational tools, risks such as exposure to inappropriate content, excessive gadget use, and declining learning focus necessitate structured and targeted mentoring. This community service activity aims to enhance TPQ students’ media literacy and to strengthen teachers’ capacity to utilize media as educational resources through an Asset-Based Community Development (ABCD) approach. The program was implemented at TPQ Baitul Halim Babatan Wiyung, Surabaya, involving approximately 30 students and three teachers. The stages of the activity included community asset mapping (discovery), formulation of shared aspirations (dream), design of mentoring modules and training programs (design), implementation of media literacy education for students and technical guidance for teachers (define/destiny), and program evaluation through reflective activities (reflection). The results indicate an improvement in students’ understanding of ethical media use, their ability to identify educational and safe content, and the emergence of basic critical attitudes toward digital information. TPQ teachers (Ustadz and Ustadzah) also demonstrated enhanced competence in selecting and integrating educational media into the learning process. This program contributes to the establishment of a positive, character-based media literacy culture grounded in Islamic values within the TPQ environment and has the potential to be developed as a sustainable mentoring model in non-formal education.